Planning visions in disaster management: the study area, Diyala Governorate - Kadhim, Fatima Muhammed (Al-Adab Journal, 2022)
This research deals with the role of planning in managing and dealing with disasters (the flood disaster), and the research problem lies in the extent and importance of the role that planning plays in disaster management. The researcher followed the integrative approach, which includes many approaches (descriptive-analytical), and the researcher benefited from the information collection tools (questionnaire form, interview) that were distributed in the study area (Diyala governorate). Disaster management by preparing to face the disaster, contain it and deal with it in a quick way and get out with the least material and moral losses.